2020
DOI: 10.1140/epjc/s10052-020-8320-0
|View full text |Cite
|
Sign up to set email alerts
|

Doubly charmed multibaryon systems

Abstract: We study two- and three-baryon systems with two units of charm looking for possible bound states or resonances. All two-baryon interactions are consistently derived from a constituent quark model tuned in the light-flavor hadron phenomenology: spectra and interactions. The presence of the heavy quarks makes the two-body interactions simpler than in the light-flavor sector. Our results show a narrow two-body resonance with quantum numbers $$(I,J^P)=(0,0^+)$$(I,JP)=(0,0+). It is located 6.2 MeV below the $$\Sigm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…In our simple model the leading order interaction for the Λ c Λ c system is repulsive and thus it cannot be bound. Within various models, it was found that the Λ c Λ c system can not be bound by itself [216][217][218][219][220][221] but Refs. [217][218][219]222] showed that the coupling to the strongly attractive Σ…”
Section: Heavy Di-baryonsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our simple model the leading order interaction for the Λ c Λ c system is repulsive and thus it cannot be bound. Within various models, it was found that the Λ c Λ c system can not be bound by itself [216][217][218][219][220][221] but Refs. [217][218][219]222] showed that the coupling to the strongly attractive Σ…”
Section: Heavy Di-baryonsmentioning
confidence: 99%
“…In Ref. [221], the potential of Σ c Σ c was derived from a constituent quark model and a bound state with I(J P ) = 0(0 + ) was obtained with a binding energy about 6.2 MeV. The long-range pion exchange force is strong enough to form molecules of…”
Section: Heavy Di-baryonsmentioning
confidence: 99%
“…Other dibaryon states have been studied, with n < 6 units of heavy flavor, and there is no evidence for stable dibaryons [63,64].…”
Section: Hexaquarksmentioning
confidence: 99%
“…The di-baryon systems that are composed of two charmed baryons are more likely to be bound, since the large reduced mass can facilitate the stabilization of such systems. As the heavy flavor siblings of the nucleon, the molecular states in the Σ c Σ c system have been investigated in a series of works [79][80][81][82][83][84][85]. In this work, we will mainly concentrate on the interactions of the Σ c Σ c system, and explore the relevance of intermediate states in the two-pion exchange (TPE) loops within the chiral effective field theory (χEFT).…”
Section: Introductionmentioning
confidence: 99%